The wolf and the crane - Michael; Dr (Chennai Mind to Mind, 2005)
In this story, a wolf gets a bone stuck in its throat and seeks help from a crane. The crane, with its long beak, successfully removes the bone, but the wolf, rather than showing gratitude, dismisses the crane and refuses to reward it. The tale teaches a valuable lesson about ingratitude and the importance of recognizing and valuing the help others provide. This book is designed to engage young readers with its simple narrative and moral while fostering early reading skills.